Carrying Capacity Analysis of Aquatic Environment in the Fishery Reserves Area of Terubuk Fish in Riau Province - Hendra Saputra; Deni Efizon; Asmika Harnalin (ECOTONE, 2020)
This study aims to determine and analyze the carrying capacity of that area and to estimate the potency of the fish based on the Net Primary Productivity (NPP) and it was conducted in February 2018. Samplings were conducted 6 times, once/ week. Parameters measured were temperature, brightness, current speed, salinity, N, P, pH, DO, and chlorophyll-a concentration. Data on sea surface temperature, PAR (Photosynthetic Active Radiation), and chl-a concentration were also obtained from Aqua MODIS provided by NASA Ocean Biology Processing Group. Based on data obtained from the field, the NPP distribution value ranged from 18.27 to 74.98 mg C/m2/day, while the NPP value that was calculated from the Aqua MODIS data was ranged from 2,208 to 3,272 mg C/m2/day.Based on field obtained data, the carrying capacity of the study area, in general, was 97.92 tons and the potency was 48.86 tons. Based on Aqua MODIS data, the carrying capacity was 7,356.02 tons and the potency was 3,678.01. In that area, the amount of T. macrura was around 40% of total capture and it can be predicted that the carrying capacity of T. macrura39.09 tons and the potency was 19.54 tons (based on field data) or the carrying capacity was 2,942.41 tons and the potency was 1,471.20 tons (based on aqua MODIS data). Results of field data-based calculation indicate that the carrying capacity and the potency of T. macrura in the study area was lead to overfishing.Keywords: fish potency,  net primary productivity (NPP), overfishing, migratory fish